Performance of Spent Garnet as sand replacement in concrete at high temperature - Zulkifli, Ikmal; Mokhatar, Shahrul Niza (Recent Trends in Civil Engineering and Built Environment, 2021)
Garnet is ideal for many commercial uses due to its potential to be recycled. The dumping millions of tonnes of spent garnet in landfills, quarries, oceans and waterways will cause the creating environmental concerns. The exponential expansion of the building industry has led to riverbeds being over-exploited. This scenario impacts the climate, including a decline in water quality, stream beds and banks' destabilisation. In this study, spent garnet used as a sand replacement to produce sustainable concrete. The research objectives are to study the effects of strength of spent garnet as sand replacement on concrete properties at high temperature and evaluate its physical properties of spent garnet. Several laboratory experiments conducted to determine the physical and its compressive strength before and after exposed to high temperature. In this study, the test for the physical properties that had been conducted were water absorption and bulk density test. Furthermore, the compressive strength test was conducted after the cube specimens of spent garnet exposed to high temperature which was 300ᴼC. In order to obtain the concrete strength of 30Mpa at 28 days, the trial mix design studied accordingly. The cube specimens of 100 x 100 x 100 mm were prepared with substitution of 0%, 10%, 20%, 30% and 40% of spent garnet as sand replacement with 0.45 of water cement ratio. All the concrete mixes containing spent garnet were produced slump of 30- 60 mm. Given the test result, the cube specimen of 40 percent of spent garnet after heated started to decrease in term of strength due to the presence of the excessive of spent garnet particles in the concrete which can weak the bond between the aggregates and the cement paste. Thus, the concrete become less dense has lower bonding strength and therefore it reduces the concrete strength.